Pengaruh Kualitas Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Maros - Michael Toding; Hafipah; Elisabeth Ambalele (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to determine and analyze the influence of work quality and work environment on employee performance at the Department of Education and Culture of Maros Regency. The research employed a quantitative approach. The population consisted of 98 employees, while the sample was determined using the Slovin formula, resulting in 50 respondents. Data were collected through the distribution of Likert-scale questionnaires, direct observation, and documentation studies. The data analysis techniques applied included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using the t-test and F-test with the assistance of the SPSS program. The results of the study indicate that the regression analysis produced the equation Y = 2.307 + 0.367X1 + 0.473X2. Based on the partial test (t-test), the work quality variable was proven to have a positive and significant effect on employee performance, with a significance value of 0.000. The work environment variable was also found to have a positive and significant effect on employee performance, with a significance value of 0.000. Furthermore, the simultaneous test (F-test) results show that work quality and work environment jointly have a positive and significant effect on employee performance at the Department of Education and Culture of Maros Regency, with an F-value of 65.139. In conclusion, employee performance is strongly influenced by work quality and the work environment.